PB1‐F2 protein of highly pathogenic influenza A (H7N9) virus selectively suppresses RNA‐induced NLRP3 inflammasome activation through inhibition of MAVS‐NLRP3 interaction - Cheung, Pak‐Hin Hinson; Ye, Zi‐Wei; Lee, Tak‐Wang Terence; Chen, Honglin; Chan, Chi‐Ping; Jin, Dong‐Yan (Journal of leukocyte biology, 2020)
Infection with seasonal as well as highly pathogenic avian influenza A virus (IAV) causes significant morbidity and mortality worldwide. As a major virulence factor, PB1‐F2 protein of IAV affects the severity of disease through multiple mechanisms including perturbation of host innate immune response. Macrophages are known to phagocytose extracellular PB1‐F2 protein aggregate, leading to hyperactivation of NLRP3 inflammasome and excessive production of IL‐1β and IL‐18. On the other hand, when expressed intracellularly PB1‐F2 suppresses NLRP3 inflammasome maturation. How extracellular and intracellular PB1‐F2 orchestrates to drive viral pathogenesis remains unclear. In this study, we demonstrated the suppression of NLRP3 inflammasome activation and IL‐1β secretion by PB1‐F2 of highly pathogenic influenza A (H7N9) virus in infected human monocyte‐derived macrophages. Mechanistically, H7N9 PB1‐F2 selectively mitigated RNA‐induced NLRP3 inflammasome activation by inhibiting the interaction between NLRP3 and MAVS. Intracellular PB1‐F2 of H7N9 virus did not affect extracellular PB1‐F2‐induced NLRP3 inflammasome maturation. In contrast, PB1‐F2 of WSN laboratory strain of human IAV effectively suppressed IL‐1β processing and secretion induced by various stimuli including NLRP3, AIM2, and pro‐IL‐1β. This subtype‐specific effect of PB1‐F2 on inflammasome activation correlates with the induction of a proinflammatory cytokine storm by H7N9 but not WSN virus. Our findings on selective suppression of MAVS‐dependent activation of NLRP3 inflammasome by H7N9 PB1‐F2 have implications in viral pathogenesis and antiviral development. Graphical H7N9 PB1‐F2 selectively suppresses MAVS‐dependent activation of NLRP3 inflammasome by inhibiting the interaction between MAVS and NLRP3.